Eimeria spp. (Apicomplexa: Eimeriidae) in Didelphis aurita Wied-Neuwied, 1826 (Didelphimorphia: Didelphidae) and description of a new species infecting this opossum - Bezerra-Santos, Marcos Antônio; Nogueira, Bárbara Cristina Félix; Ramos, Rafael Antonio Nascimento; Duszynski, Donald W.; Araújo, Jackson Victor De; Campos, Artur Kanadani (Zootaxa, 2020)
Didelphis aurita Wied-Neuwied, 1826 is a marsupial well adapted to anthropogenic activity and commonly found in urban areas of Brazil. Among the gastrointestinal parasites found in this opossum, protozoa of the genus Eimeria are frequently detected. This study investigated the biodiversity of Eimeria species infecting D. aurita in Southeastern Brazil, and provides morphological data on a newly discovered species of Eimeria. From January to June 2019, 43 D. aurita were captured, and their fecal samples were collected and evaluated by salt flotation; positive samples were allowed to sporulate in 2.5% potassium dichromate (K2Cr2O7), and detailed morphological measurements were performed to determine the species present. Thirty-two of forty-three (74.4%) opossums were infected with from one to five Eimeria spp. Four of the eimerians were described and named previously by others: Eimeria auritanensis, Eimeria caluromydis, Eimeria gambai, and Eimeria philanderi. Additionally, sporulated oocysts of a species new to science were detected. Oocysts of this new Eimeria species are spheroidal to subspheroidal, 21.7 × 20.7 (20-23 × 19-23), length/width (L/W) ratio 1.05, with a highly refractile polar granule, but lacking a micropyle and oocyst residuum. Sporocysts are ovoidal, 10.6 × 8.0 (9-12 × 7-9), L/W ratio 1.3, with a small, Stieda body and a sporocyst residuum of diffuse granules. Of the infected opossums, 5/32 (16%) were infected with only one Eimeria sp., 6/32 (19%) with two, 15/32 (47%) with three, 5/32 (16%) with four and 1/32 (3%) with five Eimerians.